Can Private Money Buy Public Science? Disease Group Lobbying and Federal Funding for Biomedical Research - Hegde, Deepak; Sampat, Bhaven (Management Science, 2015)
Private interest groups lobby politicians to influence public policy. However, little is known about how lobbying influences the policy decisions made by federal agencies. We study this through examining lobbying by advocacy groups associated with rare diseases for funding by the National Institutes of Health (NIH), the world’s largest funder of biomedical research. Disease group lobbying for NIH funding has been controversial, with critics alleging that it distorts public funding toward research on diseases backed by powerful groups. Our data reveal that lobbying is associated with higher political support, in the form of congressional “soft earmarks” for the diseases. Lobbying increases with disease burden and is more likely to be associated with changes in NIH funding for diseases with higher scientific opportunity, suggesting that it may have a useful informational role. Only special grant mechanisms that steer funding toward particular diseases, which comprise less than a third of the NIH’s grants, are related to earmarks. Thus, our results suggest that lobbying by private groups influences federal funding for biomedical research. However, the channels of political influence are subtle, affect a small portion of funding, and may not necessarily have a distortive effect on public science. This paper was accepted by Bruno Cassiman, business strategy.